MELALUI SUPERVISI AKADEMIK YANG BERKELANJUTAN DAPAT MENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SILABUS DAN RPP DI SMK NEGERI 8 BUNGO: MELALUI SUPERVISI AKADEMIK YANG BERKELANJUTAN DAPAT MENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SILABUS DAN RPP DI SMK NEGERI 8 BUNGO - ESNARIA PURBA (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This research is based on the importance of teachers planning, implementing and evaluating learning. Syllabus and lesson plans are the minimum preparation for a teacher when they want to teach. With these problems, researchers conducted research to see to what extent the academic supervision of school principals could improve teacher competence in the preparation of syllabus and lesson plans. The type of research used in this research is School Action Research, which consists of planning, implementation, observation and reflection. The subjects of this study were all teachers of SMK Negeri 8 Bungo. Data collection techniques used in this study include supervision, observation, semi-structured interviews and documentation. The results of the action show that: 1). With the increase in the number of teachers who compose the syllabus from 38.46% to 83% after academic supervision, 2) the number of quality lesson plans increased from 38.46% to 89%. So, by conducting academic supervision, it can improve teacher competence in compiling the Syllabus and RPP of SMK Negeri 8 Bungo.